2002
DOI: 10.1046/j.1525-142x.2002.02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the role that ecological and developmental constraints play in controlling disparity: examples from the crinoid and blastozoan fossil record

Abstract: It is widely believed that morphological constraints are responsible for the observed pattern of decreasing major morphological innovation in both the Metazoa and Metaphytes over geological time. This is readily seen as the decreasing trend of origination of higher taxa: phyla, classes, and orders. Currently, there are two competing evolutionary hypotheses that have been proposed to explain this phenomenon: (1) the empty ecospace hypothesis and (2) the developmental constraint hypothesis. To distinguish betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 63 publications
(96 reference statements)
3
50
2
Order By: Relevance
“…Similar patterns have been observed for both echinoderms (Foote 1996;Ciampaglio 2002) and brachiopods (Ciampaglio 2004) after mass extinctions. Contrasting shifts in character space accompanying major shifts in ecology with those seen within clades during 'background' times (sensu Jablonski 1986) might offer means of estimating general rates at which characters are 'gained' and 'lost' to clades as well as offer some clarification of the circumstances needed for rapid morphological diversification.…”
Section: Discussionsupporting
confidence: 80%
“…Similar patterns have been observed for both echinoderms (Foote 1996;Ciampaglio 2002) and brachiopods (Ciampaglio 2004) after mass extinctions. Contrasting shifts in character space accompanying major shifts in ecology with those seen within clades during 'background' times (sensu Jablonski 1986) might offer means of estimating general rates at which characters are 'gained' and 'lost' to clades as well as offer some clarification of the circumstances needed for rapid morphological diversification.…”
Section: Discussionsupporting
confidence: 80%
“…Such slowdown in other taxa has been perceived as the result of growing niche competition and saturation of the available ecological space, increased stabilizing selection on functionally integrated traits, or establishment of intrinsic (genetic or developmental) constraints (43)(44)(45)(46)(47). The Late Cretaceous/Early Tertiary interval is known to be a period of global biotic turnover, and previous studies have suggested that amphibians took opportunistic advantage of contemporary ecosystem remodeling (15,48).…”
Section: Discussionmentioning
confidence: 99%
“…Limited phylogenetic analyses have been produced, mostly for graptolites and gastropods, although some broader studies do span the boundary. The loss of morphologic disparity during this event appears to have been high, whether as measured by the major losses among graptolites, conodonts, brachiopods, and possibly nautiloids or by more quantitative studies of disparity within major clades (44,45,92,93). Using reefs as our measure of architectural complexity, there is a major loss of both reef types and carbonate production although there is little ecological impact (78,94), hence the medium ranking in Table 1.…”
Section: Application To Past Biotic Crisesmentioning
confidence: 96%